Efficacy of pharmacotherapy of system autoimmune inflammation process of combinations of ibuprofen with vinboron on the model of adjuvant arthritis of rats - Гладких, Ф.В.; Степанюк, Н.Г. (Materials of I Scientific and Practical Conference with International Participation "The Exclusion of Various Genesis and Ways of its Pharmacological Correction": abstracts (2–3 November, 2015). Pharmacology and Pharmacy. 2015. № 6 (App. 1). P. 37–38., 2015)
Efficacy of pharmacotherapy of system autoimmune inflammation process of combinations of ibuprofen with vinboron on the model of adjuvant arthritis of rats.
Hladkykh F. V., Stepanyuk N. H. Efficacy of pharmacotherapy of system autoimmune inflammation process of combinations of ibuprofen with vinboron on the model of adjuvant arthritis of rats. Materials of I Scientific and Practical Conference with International Participation "The Exclusion of Various Genesis and Ways of its Pharmacological Correction": abstracts (2–3 November, 2015). Pharmacology and Pharmacy. 2015. № 6 (App. 1). P. 37–38.
Keywords: pharmacotherapy; system autoimmune inflammation process; inflammation process; adjuvant arthritis